Analysis of Difficulties of Spanish Teachers to Improve Students’ Digital Reading Competence. A Case Study within the PISA Framework - Vázquez - Cano, Esteban (Pedagogika, 2017)
Digital technologies have changed the ways texts are produced and displayed, and those changes have a profound impact on how students read. In Spain, the results in digital reading competence are below the OECD average, which proves to be a handicap for Spanish students. This article presents a case study in which we investigate, through a quantitative methodology, teachers’ perceptions on the main constraints for the effective development of a teaching methodology to improve digital reading competence of secondary students in Spain. The findings show how learning processes based on digital reading are still underdeveloped and teaching staff in a large majority expresses lack of preparation, training, and resources available in the school for the effective development of a teaching that encourages successful digital reading proficiency of students. It is important for governments, teachers, and students to meet these challenges as they affect almost every aspect of our daily routines.